Estética e ideología: Perspectivas comunicacionales - Casallo, Víctor (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
The “ideology” notion has been decontextualized from its critical function to be employed as a discrediting maneuver that disregards debate. This article posits ideological analysis within the basic idea of a critical theory to point out the problems inherent to its dependency to the modern subjectivity paradigm. Afterdiscussing two attempts to preserve some form of ideological analysis by means ofa reconsideration of the aesthetical, we claim the pertinence of a communicationalinterpretation of the critic, ideology and aesthetics notions, which refers them to its founding and normative dimension in the very constitution of the self and its community.

La noción de ideología se ha descontextualizado de su función crítica para emplearse como una descalificación que prescinde del debate. En este artículo,situamos el análisis ideológico al interior de la idea básica de una teoría crítica para mostrar los problemas inherentes a su dependencia del paradigma moderno de lasubjetividad. Asimismo, luego de discutir dos esfuerzos por mantener alguna formade análisis ideológico a través de una reconsideración de lo estético, argumentamosla pertinencia de una interpretación comunicacional de las nociones de crítica, ideología y estética, que las refiera a su dimensión fundante y normativa en la constitución misma del yo y su comunidad.
Aesthetics and ideology: communicational perspectives
Keywords: Ideología; Teoría crítica; Estética; Fenomenología de la comunicación; Husserl; Arendt; https://purl.org/pe-repo/ocde/ford#5.09.01